Phymaturus roigorum: predation - Corbalán, Valeria Elizabeth (2024)
The genus Phymaturus is comprised of 52 species of saxicolous lizards that have flattened bodies and spiny tails that enable them to seek refuge in rock crevices to evade predators (Debandi et al. 2012. Austral Ecol. 37:392–400; Uetz et al. [eds.] 2024. The Reptile Database. http://www.reptile-database.reptarium.cz, 13 May 2024). Despite the high species diversity of the genus Phymaturus, little is known about the predators of most species. Known predators include birds such as Geranoaetus polyosoma (Red-backed Hawk) on P. extrilidus (Perez et al. 2013. Herpetol. Rev. 44:679), Agriornis montanus (Black-bellied Shrike-tyrant) on P. maulense (Ramírez-Álvarez and Cox 2023. Herpetol. Notes 16:391–394), and Circus cinereus (Cinereous Harrier; Martínez, pers. comm.) on P. verdugo, although the mammal Galictis cuja (Lesser Grison) and the lizard Pristidactylus nigroiugulus have been reported to prey on P. spurcus (Cabezas-Cartes et al. 2013. J. Exp. Zool. 9999A:1–9; Cabezas-Cartes et al. 2018. J. Zool. 304:175–181). Here, we report an observation of a Lycalopex gymnocercus (Pampas Fox) preying on the endemic P. roigorum at the Payunia Reserve in Mendoza Province, Argentina (36.4856°S, 69.3713°W; WGS 84; 2107 m elev.).